Beta‐amyloid and cognitive decline in late middle age: Findings from the Wisconsin Registry for Alzheimer's Prevention study. Issue 7 (21st January 2016) - Clark, Lindsay R.; Racine, Annie M.; Koscik, Rebecca L.; Okonkwo, Ozioma C.; Engelman, Corinne D.; Carlsson, Cynthia M.; Asthana, Sanjay; Bendlin, Barbara B.; Chappell, Rick; Nicholas, Christopher R.; Rowley, Howard A.; Oh, Jennifer M.; et al.
Abstract: Introduction: The present study investigated the relationship between beta‐amyloid (Aβ) and cognition in a late middle‐aged cohort at risk for Alzheimer's disease (AD). Methods: One eighty‐four participants (mean age = 60; 72% parental history of AD) completed a [C‐11]Pittsburgh compound B positron emission tomography scan and serial cognitive evaluations. A global measure of Aβ burden was calculated, and composite scores assessing learning, delayed memory, and executive functioning were computed. Results: Higher Aβ was associated with classification of psychometric mild cognitive impairment (MCI) at follow‐up ( P  < .01). Linear mixed effects regression results indicated higher Aβ was associated with greater rates of decline in delayed memory ( P  < .01) and executive functioning ( P  < .05). Apolipoprotein E ( APOE ) ε4 status moderated the relationship between Aβ and cognitive trajectories ( P  values <.01). Discussion: In individuals at risk for AD, greater Aβ in late middle age is associated with increased likelihood of MCI at follow‐up and steeper rates of cognitive decline.